Design of hybrid precoding with successive interference cancellation and alternating direction method of multipliers - Xiongwen ZHAO; Yao LIU; Yu ZHANG; Suiyan GENG; Peng QIN; Zhenyu ZHOU (Tongxin xuebao)
To solve the problem of large power consumption caused by a large number of phase shifter (PS) in millimeter wave multi-antenna systems, a new type of dynamic connection structure was designed.With the goal of maximizing spectrum efficiency, two hybrid precoding schemes, successive interference cancellation (SIC) and successive interference cancellation-alternating direction multiplier (SIC-ADMM), were proposed.In SIC scheme, the sum-rate problem was decomposed into multiple sub-rate problems of different radio frequency links, the analog part was solved by iteration, and the digital part was solved by a low-dimensional equivalent matrix.Based on SIC scheme, an improved SIC-ADMM scheme was further proposed by studying the multi-variable sub-rate problem to achieve rapid convergence and reduce computational complexity effectively.The simulation results show that the proposed schemes have good spectrum and energy efficiencies by comparison with the existing schemes, and are more suitable for large-scale antenna systems.In addition, when a certain percentage of PS is turned off, the proposed scheme can greatly improve energy efficiency by sacrificing a small amount of spectrum efficiency.